2017
DOI: 10.1007/978-3-319-60189-2_8
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Activation of Microglia and Astrocytes in Manganese Neurotoxicity

Abstract: Neurotoxicity due to excessive exposure to manganese (Mn) has been described as early as 1837 (Couper, Br Ann Med Pharm Vital Stat Gen Sci 1:41-42, 1837). Extensive research over the past two decades has revealed that Mn-induced neurological injury involves complex pathophysiological signaling mechanisms between neurons and glial cells. Glial cells are an important target of Mn in the brain, both for sequestration of the metal, as well as for activating inflammatory signaling pathways that damage neurons throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 114 publications
(234 reference statements)
4
63
0
1
Order By: Relevance
“…Moreover in the GFAP‐positive astrocytes, the relative increase in the A1 proinflammatory astrocyte marker C3 (to ~568% of controls) was ~2.8‐fold greater than the anti‐inflammatory A2 marker S100A10 (200% of controls), suggesting an overall proinflammatory neuroenvironment in the mPFC; this interpretation assumes that the proportional increase in C3 versus S100A10 protein levels in GFAP‐positive astrocytes directly reflects the relative increase in A1 and A2 cell phenotypes. Prior in vivo and in vitro studies have previously shown that Mn exposure may promote the reactivity of astrocytes and microglia to contribute to neuroinflammation, as measured by increased proinflammatory gene and protein expression, along with higher levels of proinflammatory cytokines (Jin et al, ; Kern & Smith, ; Liu, Sullivan, Madl, Legare, & Tjalkens, ; Popichak et al, ; Zhao et al, ; Tjalkens, Popichak, & Kirkley, ). Furthermore, Liddelow et al () recently demonstrated that reactive astrocytes exhibiting an A1 proinflammatory phenotype led to loss of synaptic function, increased synaptic pruning, impaired endocytosis of extracellular debris, and an increased risk for neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover in the GFAP‐positive astrocytes, the relative increase in the A1 proinflammatory astrocyte marker C3 (to ~568% of controls) was ~2.8‐fold greater than the anti‐inflammatory A2 marker S100A10 (200% of controls), suggesting an overall proinflammatory neuroenvironment in the mPFC; this interpretation assumes that the proportional increase in C3 versus S100A10 protein levels in GFAP‐positive astrocytes directly reflects the relative increase in A1 and A2 cell phenotypes. Prior in vivo and in vitro studies have previously shown that Mn exposure may promote the reactivity of astrocytes and microglia to contribute to neuroinflammation, as measured by increased proinflammatory gene and protein expression, along with higher levels of proinflammatory cytokines (Jin et al, ; Kern & Smith, ; Liu, Sullivan, Madl, Legare, & Tjalkens, ; Popichak et al, ; Zhao et al, ; Tjalkens, Popichak, & Kirkley, ). Furthermore, Liddelow et al () recently demonstrated that reactive astrocytes exhibiting an A1 proinflammatory phenotype led to loss of synaptic function, increased synaptic pruning, impaired endocytosis of extracellular debris, and an increased risk for neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Manganism is a neurodegenerative disease of the cerebral cortex and basal ganglia caused by excessive exposure to Mn [42,43]. Neuroinfl ammatory activation plays roles in both the progression of manganism and the promotion of neurological damage from both acute and chronic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…These glial markers are widely studied in Huntington's and Parkinson's disease [58], multiple sclerosis [59], amyotrophic lateral sclerosis-ALS [58,60] and Alzheimer's disease [58,[60][61][62] as their expression changes in response to activation or differentiation. Activated glia may either become neuroprotective or neurotoxic, depending on the cytokines, chemokines, or growth factors that are released [63]. If neurotoxic, disruption in neuronal signaling and neuronal loss can lead to a number of neurological deficits including cognitive impairment and motor dysfunction.…”
Section: Discussionmentioning
confidence: 99%